Multiple Molecular Pathways in Melanomagenesis: Characterization of Therapeutic Targets - Palmieri, Giuseppe; Ombra, MariaNeve; Colombino, Maria; Casula, Milena; Sini, MariaCristina; Manca, Antonella; Paliogiannis, Panagiotis; Ascierto, Paolo Antonio; Cossu, Antonio (Frontiers in Oncology, 2015)
Molecular mechanisms involved in pathogenesis of malignant melanoma have been widely studied and novel therapeutic treatments developed in recent past years. Molecular targets for therapy have mostly been recognized in the RAS–RAF–MEK–ERK and PI3K–AKT signaling pathways; small-molecule inhibitors were drawn to specifically target key kinases. Unfortunately, these targeted drugs may display intrinsic or acquired resistance and various evidences suggest that inhibition of a single effector of the signal transduction cascades involved in melanoma pathogenesis may be ineffective in blocking the tumor growth. In this sense, a wider comprehension of the multiple molecular alterations accounting for either response or resistance to treatments with targeted inhibitors may be helpful in assessing, which is the most effective combination of such therapies. In the present review, we summarize the known molecular mechanisms underlying either intrinsic and acquired drug resistance either alternative roads to melanoma pathogenesis, which may become targets for innovative anticancer approaches.